PROSPECTS FOR THE USE OF GENOTYPING FOR CHROMOSOME 9p21.3 POLYMORPHISMS FOR MYOCARDIAL INFARCTION RISK STRATIFICATION IN YOUNG PEOPLE - P. A. Shesternya; S. Yu. Nikulina; V. A. Shulman; E. A. Martynova; A. I. Demkina; V. V. Kozlov (Klinicist)
Objective: to study whether genotyping for single nucleotide polymorphisms (SNPs) rs10757278 and rs1333049 on the 9p21.3 locus may be applied to myocardial infarction (MI) risk stratification using the SCORE scale in young people (less than 45 years).Subjects and methods. A group of patients with MI (n = 103) and a control group (n = 111) showed no statistically significant differences ingender, age, hypertension, diabetes mellitus, hypercholesterolemia, overweight and obesity, abdominal obesity, and smoking history. The phenolchloroform method was employed to extract genomic DNA from venous blood. Genetic tests were carried out using real-time polymerasechain reaction systems (TagMan and AB 7900HT).Results. There was a statistically significant association of rs1333049 and rs 10757278 with the development of MI. The odds ratio for the latter was 2.53 (95 % confidence interval (CI) 1.31-4.89) in carriers of the risk allele C of rs1333049 and 2.11 (95 % CI 1.11–4.01) in those with the risk allele G of rs10757278. The statistical significance also remained with consideration for the family history of MI. Multiple logistic regression analysis established that the presence of the C allele of rs1333049 in the genotype was of great predictive value as compared with the high/very high risk of fatal and nonfatal events according to the SCORE scale.Conclusion. SNPs 1333049 and rs10757278 on the 9p21.3 locus are the predictors of MI in young people, which are independent of both traditional risk factors and family history. Having regard to the pattern of an association, it will suffice to genotype one of them, namely rs 1333049, in our population